2017
DOI: 10.1038/s41598-017-08267-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor ZNF148 is a negative regulator of human muscle differentiation

Abstract: Muscle differentiation is a complex process in which muscle progenitor cells undergo determination and eventually cellular fusion. This process is heavily regulated by such master transcription factors as MYOD and members of the MEF2 family. Here, we show that the transcription factor ZNF148 plays a direct role in human muscle cell differentiation. Downregulation of ZNF148 drives the formation of a muscle phenotype with rapid expression of myosin heavy chain, even in proliferative conditions. This phenotype wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In total, 31 known TFBS were predicted to have the binding motifs in at least one SINE family, 30 of which (96.8%) were found in old ones and 26 (83.9%) were related to the open chromatin, revealing that the recent exaptation of young SINEs into regulatory regions was relatively rare 71 and was repressed by less chromatin accessibility. The youngest SINE-specific TFBS related to the ZNF148 gene has been proven to drive the formation of a muscle phenotype 72 . Besides, three members of the RFX transcription factor family were observed to be amplified in young and older SINEs and involved in the immune, reproductive, and nervous pathways 73 .…”
Section: Resultsmentioning
confidence: 99%
“…In total, 31 known TFBS were predicted to have the binding motifs in at least one SINE family, 30 of which (96.8%) were found in old ones and 26 (83.9%) were related to the open chromatin, revealing that the recent exaptation of young SINEs into regulatory regions was relatively rare 71 and was repressed by less chromatin accessibility. The youngest SINE-specific TFBS related to the ZNF148 gene has been proven to drive the formation of a muscle phenotype 72 . Besides, three members of the RFX transcription factor family were observed to be amplified in young and older SINEs and involved in the immune, reproductive, and nervous pathways 73 .…”
Section: Resultsmentioning
confidence: 99%
“…MEF2C is involved in cardiac myogenesis and morphogenesis, as well as vascular development. 40,41 Moreover, some studies have indicated that MEF2C may play a much broader biological role in the generation of tissues other than cardiac and skeletal muscle. For example, this gene may also be involved in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…HSMM and SKMC cells were purchased from Lonza (Allendale, NJ) and cultivated according to manufacturer protocol. LHCN-M2 cells were grown as previously described 28 , 29 . The RD, RH30, and 293T cell lines were obtained from ATCC (Manassas, VA).…”
Section: Methodsmentioning
confidence: 99%